Factores sociodemográficos económicos y su relación con la gestión de las finanzas personales en los docentes del Colegio Cooperativo César Vallejo Iquitos, 2023 - Bardales Isla, Angel Armando (2023)
The purpose of this research was to establish the relationship that exists between sociodemographic and economic factors with the management of personal finances in the teachers of the César Vallejo Cooperative College, Iquitos, 2023. The type of research was descriptive - relational, observational and analytical, design was non-experimental - transversal. Population made up of 85 workers, the sample being 31 teachers from the César Vallejo Cooperative College. The instrument was validated by expert judgment and the reliability for the collection of information was verified. The SPSS v25 software was used to analyze the information, achieving the following results: personal finance management was moderate in 71%, adequate in 16.1% and deficient in 12.9%, the personal budget, 58.1% showed adequate level, 35.5% moderate and 6.5% deficient, family budget, 77.4% was moderate, 12.9% deficient and 9.7% adequate, Financial intelligence, 71% was moderate, 22.6% deficient and 6.5% adequate. It concludes: There is evidence of a significant relationship between the level of education and the management of personal finances (X2C =11.117; gl=2; p=0.004< 0.05). However, Age, Sex, Marital Status, Employment Status and Service Time are not related to personal finance management (p>0.05).